1998
DOI: 10.1002/(sici)1096-9861(19980810)397:4<493::aid-cne4>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Different origins and developmental histories of transient neurons in the marginal zone of the fetal and neonatal rat cortex

Abstract: Two major classes of early-born neurons are distinguished during early corticogenesis in the rat. The first class is formed by the cortical pioneer neurons, which are born in the ventricular neuroepithelium all over the cortical primordium. They appear at embryonic day (E) 11.5 in the lateral aspect of the telencephalic vesicle and cover its whole surface on E12. These cells, which show intense immunoreactivity for calbindin and calretinin, are characterized by their large size and axonal projection. They rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(110 citation statements)
references
References 54 publications
7
103
0
Order By: Relevance
“…7a, b and Table 2). Most authors consider that the origin of this stream in mammals resides in the MGE (Lavdas et al 1999;Corbin et al 2001;Wichterle et al 2001), although the retrobulbar and LGE origins have also been considered (Gadisseux et al 1992;Meyer et al 1998;Jiménez et al 2002). In our hands, expression of Dlx2 in the pallium was visibly continuous with that found in the LGE-h, which may indicate that the origin of this proposed route in sharks is the LGE-h.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…7a, b and Table 2). Most authors consider that the origin of this stream in mammals resides in the MGE (Lavdas et al 1999;Corbin et al 2001;Wichterle et al 2001), although the retrobulbar and LGE origins have also been considered (Gadisseux et al 1992;Meyer et al 1998;Jiménez et al 2002). In our hands, expression of Dlx2 in the pallium was visibly continuous with that found in the LGE-h, which may indicate that the origin of this proposed route in sharks is the LGE-h.…”
Section: Discussionmentioning
confidence: 47%
“…In mammals, a similar transient migration has been described, and it is the origin of subpial granule neurons that invade the marginal zone of the dorsal pallium to become integrated in the layer I of the developing neocortex (Gadisseux et al 1992;Meyer et al 1998;Lavdas et al 1999;Corbin et al 2001;Wichterle et al 2001;Morante-Oria et al 2003), where they express GABA and Reelin (Meyer et al 1998;Lavdas et al 1999;Antypa et al 2011). Although the neocortex is a mammalian novelty, it has been demonstrated that the tangential migration of interneurons is astonishingly conserved throughout evolution (Cobos et al 2001;Métin et al 2007;Carrera et al 2008;Moreno et al 2008;Mueller et al 2008;Wullimann 2009).…”
Section: Discussionmentioning
confidence: 81%
“…1A). Meyer et al (1998) recently described in developing rat cortex two major classes of early generated neurons in the marginal zone/layer I: 1) the so-called cortical pioneer neurons, which are only present in prenatal cortex, and 2) the so-called subpial granule neurons, which may differentiate into Cajal-Retzius cells during the early postnatal period. Because all of our recordings were performed in postnatal cortex and the cells in our sample were located in a deeper position in layer I, we classify this group of cells as Cajal-Retzius neurons.…”
Section: Identification Of Cellsmentioning
confidence: 99%
“…Our previous studies in mouse indicate that many of these interneurons -including those containing calciumbinding proteins -appear to immigrate into the basolateral amygdala since early developmental stages, and their local circuits start to develop before birth (Legaz et al, 2005b). Calbindin-immunopositive (CB+) neurons are one of the most abundant and earliest cell types identified in the embryonic basolateral amygdala, similarly to other parts of the pallium (Meyer et al, 1998;Dávila et al, 2005;Legaz et al, 2005a,b). For this reason, this cell type is often analyzed in studies of tangential migration of interneurons from the subpallial ganglionic eminences to the pallial/cortical regions (for example, Anderson et al, 1997;Nery et al, 2002;Legaz et al, 2005a).…”
Section: Introductionmentioning
confidence: 98%